Home health care in Japan: A call of the raised voice - Cahyani, Nindhi Zuhria; Shintaro, Watanabe (Innovation in Health for Society, 2021)
Providing home care to older people remains challenging in Asia countries such as Japan. The different cultures lead nurses to assist in different ways of care. As a nurse from abroad, delivering nursing care in other country need specific skills and knowledge to optimize the care. In addition, innovation is also needed for its efficiency during elderly care. Hopefully, this experience will motivate nurses to work in-home care service with heart instead of relocating to a retirement or long-term care facility as they get older. "Ageing in place" refers to remaining in the familiar surroundings of your home for as long as is physically possible. If you only need minimal assistance with your day-to-day activities, have a tight network of family and friends in the area, and can utilize the appropriate home care services to cover your needs, staying in your home as you age may be a reasonable option. Investigate the various services at your disposal. You can determine whether or not remaining in your home as you age is the most advantageous way to keep your independence and make the most of your golden years. Keywords: Elderly care; nursing; community nurses; innovation in nursing; society care